Risk of Mortality after Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at University College and Great Ormond Street Hospital, and other members of the North London Epilepsy Research Network investigated the mortality within 8 years following an episode of childhood convulsive status epilepticus and its predictors in a prospective, population-based study from north London, UK.